Disparity of the Waiting Period of the Capital Punishment Execution for Narcotics and Murder Cases in the Perspective of Human Rights - Djernih Sitanggang; Efa Laela Fakhriah (Jurnal Dinamika Hukum, 2019)
Disparity of the waiting period of the capital punishment execution for narcotics and murder cases occurs as the legal consequence of the policy of the Indonesian Public Prosecution Service for prioritizing the execution of death row inmates in narcotics cases. The problem is how the analysis is in the perspective of Human Rights for such disparity of the waiting period for the execution of the death row inmates as a result of the Prosecutor's policy to prioritize the execution of the death row inmates in narcotics cases. This study uses a juridical normative method with the legislation and case approaches. The study's result concludes that disparity of the waiting period for the execution of death row inmates in narcotics and murder cases represents no protection and respect for human rights. There should be an implementing regulation that governs the waiting period of the execution of death row inmates to avoid the disparity, so that execution of death row inmates will be carried out to represent the human rights protection.Keywords: Disparity, Waiting Period of Execution, Death Row Inmate, Human Rights